2005
DOI: 10.1093/schbul/sbi025
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of First-Episode Psychosis: Illustrating the Challenges Across Diagnostic Boundaries Through the Cavan-Monaghan Study at 8 Years

Abstract: The epidemiology of first-episode psychosis is poorly understood because of the paucity of systematic studies, yet it constitutes the fundamental basis for understanding the disorder and the foundations on which clinical, biological, therapeutic, and long-term outcome studies are built. A particular need is to clarify the diagnostic breadth of first-episode psychosis and, on this basis, to undertake systematic comparisons across representative populations of the psychoses, to include comparisons with first-epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
136
4
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(157 citation statements)
references
References 87 publications
5
136
4
3
Order By: Relevance
“…34 In a recent Irish study, the annual incidence of all psychoses in people aged over 15 years was estimated to be 0.32 per 1000. 35 In a study of adolescents aged up to 18 years, the 3-year reported incidence of ICD-10 functional psychosis was 5.9 per 100,000, 2 which equates to…”
Section: Incidence Of Psychosismentioning
confidence: 99%
“…34 In a recent Irish study, the annual incidence of all psychoses in people aged over 15 years was estimated to be 0.32 per 1000. 35 In a study of adolescents aged up to 18 years, the 3-year reported incidence of ICD-10 functional psychosis was 5.9 per 100,000, 2 which equates to…”
Section: Incidence Of Psychosismentioning
confidence: 99%
“…Discrepancies between this work and other studies may be attributable to examining data in small cohorts (aver age of 24.3 patients with psychosis and 25.6 controls based on a review of DTI findings in recentonset psychosis 2 ) using voxelbased methods, which can be affected by registration confounds, 58 and the lack of studies mapping specific tract anatomy within study participants. 59 Our analysis grouped 4 subcategories of psychosis together (i.e., schizophrenia spectrum psychosis 60 ), though there is argument as to whether schizoaffective disorders fall within or apart from this grouping. While this grouping enables the analysis of the shared components that give rise to the symptoms and neuro cognitive deficits in emerging psychosis as a whole, larger studies should examine the white matter differences between patients with affective and nonaffective psychoses, taking into account the age at onset of affective, positive and negative symptoms.…”
Section: Limitationsmentioning
confidence: 99%
“…Patients were drawn from attendees of Cavan-Monaghan Mental Health Service who were under the age of 65; each satisfied DSM-IV criteria (American Psychiatric Association 1994) for schizophrenia or schizoaffective disorder as described previously Baldwin et al 2005). Control subjects under the age of 65 were drawn from individual and community group volunteers in CavanMonaghan; on semi-structured interview with the same psychiatrist who assessed patients, those individuals giving a personal or family history of psychotic illness or suicide in a first degree relative were excluded.…”
Section: Subjectsmentioning
confidence: 99%